Staff Perceptions on the Implementation and Delivery of the Active Education Beyond the School Day Programme in Wales, United Kingdom (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: Low levels of physical activity and high sedentary behaviour among children and young people remain a global public health concern, with youth in Wales (United Kingdom) reporting some of the lowest physical activity levels worldwide. Schools are recognised as critical environments for promoting health and wellbeing, both during and beyond the school day. Active education settings which involve access to sport and physical activity opportunities beyond the school day through the utilisation of school facilities are increasingly viewed as a strategy to address these challenges. This study aimed to explore staff perceptions of the implementation and delivery of a Sport Wales programme “Active Education Beyond the School Day” (AEBSD). Methods: A mixed-methods evaluation was conducted between March and September 2022, with 13 schools participating in the AEBSD programme. Structured interviews were conducted with 11 staff across eight schools, including school leaders, teachers, and sport development personnel. Data collection was guided by a co-developed questionnaire addressing six thematic areas. Closed responses were analysed descriptively, and open-text responses through qualitative content analysis.Results: Staff reported multiple perceived benefits of the programme, including increased physical activity levels, enhanced student wellbeing, strengthened school-community partnerships, and greater inclusivity. Diverse activity offerings, late transport provision, and targeted engagement with specific groups, such as children with disabilities and LGBTQ+ students, were highlighted as important considerations. Challenges included delayed facility readiness, funding and budgeting issues, staffing constraints, and difficulties sustaining community engagement.Conclusion: Despite the barriers identified, the AEBSD programme was perceived positively by school and local authority staff, demonstrating the potential for schools to function as community hubs for promoting physical activity and subsequently wellbeing. The programme fostered inclusive participation, improved community cohesion, and supported curriculum-linked educational outcomes. Addressing the reported barriers, particularly around funding timelines, staffing capacity and community coordination will be essential for sustaining and scaling up the programme. These findings contribute to the growing evidence base supporting extended school use and highlight key considerations for embedding active education models in policy and practice.